CONSOLIDATED BIOPROCESS BY CLOSTRIDIUM THERMOCELLUM DSM 1313 IN IN SITU STERILISABLE STIRRED TANK FERMENTER FOR ENHANCED DIGESTIBILITY AND INCREASED BIOETHANOL PRODUCTION FROM SUGARCANE BAGASSE - NISHA MUKUND,; MUKUND SHANKAR,; SARANYAH .K,; LILLY M.SALEENA, (International Journal of Pharma and Bio Sciences, 2016)
Consolidated bioprocess by Clostridium thermocellum DSM1313 is studied here for the hydrolysis of pre-treated sugarcane bagasse and banana pseudostem for ethanol production. Ethanol titre of 26.27 and 9.12mM and release of 4.770±0.107and 3.281±0.109g/L of reducing sugars from sugarcane bagasse and banana pseudostem respectively were observed in flask level studies. Sugarcane bagasse was taken further for scale-up studies in a 3L in situ sterilisable industrial fermenter. An increased growth rate with two fold increase in release of reducing sugars and a final ethanol titre of 54.35mM highlights the efficient hydrolysis of the substrate not only by the organism but also due to the direct steam-substrate contact during sterilisation. Due to the thermophilic conditions of the broth, ethanol recovery was found to be 3.43% efficient than the control. This paper emphasizes the importance of a controlled environment for efficient lignocellulosic hydrolysis, and an energy efficient ethanol recovery.